2012
DOI: 10.1111/j.1558-5646.2012.01607.x
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Reproductive Isolation in Nolana (Chilean Bellflower)

Abstract: We examined reproductive isolating barriers at four postmating stages among 11 species from the morphologically diverse genus Nolana (Solanaceae). At least one stage was positively correlated with both genetic and geographic distance between species.Postzygotic isolation was generally stronger and faster evolving than postmating prezygotic isolation. In addition, there was no evidence for mechanical isolation, or for reproductive character displacement in floral traits that can influence pollinator isolation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
81
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 52 publications
(89 citation statements)
references
References 66 publications
(113 reference statements)
7
81
0
1
Order By: Relevance
“…This is consistent with the original study in the sense that only geographical distance was significant using the Mantel test (Jewell et al., 2012). The analysis using the genetic distance matrix also indicated that geographic distance was the only significant predictor of reproductive isolation (Table 4), and the coefficients were similar to the previous analysis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This is consistent with the original study in the sense that only geographical distance was significant using the Mantel test (Jewell et al., 2012). The analysis using the genetic distance matrix also indicated that geographic distance was the only significant predictor of reproductive isolation (Table 4), and the coefficients were similar to the previous analysis.…”
Section: Resultsmentioning
confidence: 99%
“…The topology on the right was generated using Ward's hierarchical clustering method for pairwise genetic distances reported in Jewell et al. (2012)…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reproductive traits and reproductive isolation are both ecologically important and genetically tractable in our study groups, and in other close relatives (Smith et al 2008;Jewell et al 2012).…”
Section: Synthesis: Comparative Ecological Genomics Of Reproductive Tmentioning
confidence: 99%
“…To address these potential collateral effects of rapid mating trait divergence, we require studies that examine multiple reproductive barriers among closely related taxa that differ in such trait(s), and are therefore able to simultaneously assess the relative importance of this divergence versus other axes of differentiation that might drive isolation between lineages (e.g. Jewell et al 2012; Martin and Mendelson 2016). …”
Section: Introductionmentioning
confidence: 99%